Взаємозв’язок та взаємоузгодженість основоположних принципів права та нетипових соціальних регуляторів - Гольцова, О.Є. (Альманах права, 2012)
У статті досліджується взаємоузгодженність основоположних принципів права та нетипових соціальних регуляторів. Розглядається взаємозв’язок права та нетипових соціальних регуляторів як складових регулятивної системи суспільних відносин. Розкривається природа, поняття, значення, функціональне призначення нетипових соціальних регуляторів, серед яких правові презумпції, правові фікції та правові аксіоми, їх вплив на функціонування, розвиток та вдосконалення правової системи. В статье исследуется согласованность основополагающих принципов и нетипичных социальных регуляторов. Рассматривается взаимосвязь права и нетипичных социальных регуляторов, как составляющих регулятивной системы общественных отношений. Раскрывается природа, понятие, значение, функциональное назначение нетипичных социальных регуляторов, среди которых правовые презумпции, правовые фикции и правовые аксиомы, их влияние на функционирование, развитие и совершенствование правовой
системы. Life in modern society is very diverse. It is constantly having a variety of life situations and participants in these relationships have different goals and interests. So it is natural that in the long period of historical development of human society it has formed a certain system of normative and non-normative (non-typical) regulators. The normative includes regulators that set a clear framework of public relations behaviour of participants. The system of normative regulators comprise the laws, moral, corporate, political, conventional, traditional norms and so on. All normative regulators interact to each other as well as with the so-called non-normative or non-typical social regulators. Among them are special value which belongs to the legal presumption, the legal fictions and the legal axioms. Their interaction is due to the fact that the normative social regulators and non-typical social regulators are based on principles such as justice, equality, freedom and humanism. The author explores consistency of the fundamental principles of law and non-typical social regulators. It is examined the interconnection of law and non-typical social regulators as regulatory components of the system of social relations. It reveals the nature of the concept, value, functionality of the non-typical social regulators as the legal presumption, legal fiction and legal axioms, their impact on the functioning, development and improvement of the legal system.